New flight regimes and exposure to aircraft noise: Identifying housing price effects using a ratio-of-ratios approach - Stefan Boes; Stephan Nüesch (University of Zurich, Socioeconomic Institute, 2009)
In October 2003, a new flight regime was introduced at Zurich airport that significantly changed the levels of noise pollution in surrounding communities. We investigate the impact of the new flight policy on apartment prices using a hedonic price model and a non-linear difference-in-differences identification strategy. Our results suggest that rental prices increased by about 3 to 8 percent less in regions affected by the policy change, controlling for several apartment and location characteristics. The noise discount is still significant, although smaller, even after the inclusion of object-speciffc fixed effects. However, we do not find evidence of price changes in the sales market.
Keywords: C21; Q53; R21; 330; quasi-experimental data; housing market; aircraft noise; hedonic approach; non-linear difference-in-differences; policy evaluation; Luftverkehr; Lärm; Immobilienpreis; Hedonischer Preisindex; Wohnungsmarkt; Luftverkehrspolitik; Zürich (Stadt)